Harmonic Vibration Suppression of MSCSG Based on Normalized-Variable-Step- Size LMS Algorithm - Han, Wenjing; Cai, Yuanwen; Han, Wenting; Ren, Yuan; Wang, Weijie; Yu, Chunmiao; Yin, Zengyuan (IEEE sensors journal, 2024)
When the rotor is rotating at high speed, magnetically suspended control and sensitive gyroscope (MSCSG) will generate synchronous and multifrequency vibration due to rotor mass unbalance and sensor runout, which will affect the measurement accuracy of output torque and attitude angular velocity. In order to suppress the above unbalanced vibration, first, the dynamic model of MSCSG with unbalance vibration torque is established, and the influence of unbalance vibration on the measurement accuracy of attitude angular velocity is analyzed. Then, combined with the strong coupling characteristics of two tilt channels, an unbalance vibration suppression method based on arsinh function of normalized variable step size LMS (arsinh-NLMS) algorithm is proposed, which can adjust the step size according to different frequency components to improve the convergence rate. The arsinh function is used to ensure that there is a small error in the steady-state and the normalization process reduces the sensitivity of the algorithm to the input signal and tracks the harmonic components of the control current better. Finally, the simulation and experimental results show that the proposed method can effectively suppress the synchronous and multifrequency disturbance currents and vibration torques in MSCSG and reduce the influence of unbalance vibration on MSCSG performance and angular velocity measurement accuracy.